EFFECTS OF RICKSHAWS AND AUTO-RICKSHAWS ON THE CAPACITY OF URBAN SIGNALIZED INTERSECTIONS - Md. Mizanur RAHMAN (IATSS Research, 2004)
Non-motorized vehicles (i.e. rickshaws) and small size motorized vehicles (i.e. auto-rickshaws) are popular para-transit modes that provided door-to-door service in congested parts of Dhaka metropolitan area. Improper design of signal timing at signalized intersections is one of the reasons of traffic congestion in Dhaka metropolitan area. For capacity analysis, to convert the mixed traffic flow into basic traffic flow passenger car equivalents plays an important role. In Bangladesh for signal design purposes passenger car equivalents value of rickshaws and auto-rickshaw are assumed by the traffic engineers as there is no widely acceptable method to estimate PCE values of rickshaws and auto-rickshaws, which is likely to result in unnecessarily long queues and additional delays or, in other words, inefficient intersection control. The objective of this study was to analyze the effects of rickshaws and auto-rickshaws on the capacity of signalized intersections. This study also aimed at developing an estimation method of passenger car equivalent of rickshaws and auto rickshaws at signalized intersections by a macroscopic approach. Data of four intersections of Dhaka metropolitan were used for development of PCE values. Passenger car equivalent values of rickshaws and auto-rickshaws are recommended for capacity analysis of urban signalized intersections with a mixed traffic flow. The results indicated that the estimated PCE value of rickshaws and auto rickshaws of this study are different from the assumed PCE values that are presently used by traffic engineers of Bangladesh.